Gamification Strategy in Entrepreneurship Course - Wangi, Nisaul Barokati Seliro; Rochman, Kholil Lur; Saifillah, M Shoffa; Yuliani, Endah; Hariyadi, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The Gamification strategy plays an important role in determining students' learning achievement in the learning process. The entrepreneurship courses include the Understanding and appreciation of entrepreneurship, the role of entrepreneurial mental attitude for self-improvement and entity entrepreneurship through introducing the entrepreneurial characteristics, managing business interests and providing tips of successful entrepreneurs, creating business plans and making business plans. The goal of this course is to provide understanding and appreciation to the students about entrepreneurship. This developmental research used a gamification strategy on the entrepreneurship course in Indonesian Language and Literature study program, Faculty of Teacher Training and Education, UNISDA Lamongan. Gamification strategy was developed into four basic components, such as; the rules of gamification, feedback (leaderboards, prizes, and medals), objectives, and challenges. This study used lee's and Owen's development research as follows: (1) needs, (2) pre-test and post-test analysis, (3) design, (4) development, (5) implementation, (6) evaluation. The results of this game were (1) gamification strategy (2) Lecturer guide (3) student guide (4) entrepreneurship Book.